The Prader-Willi syndrome with a 15/15 translocation. Case report and review of the literature. - Hawkey, C J (1976)
A case, diagnosed clinically as the Prader-Willi syndrome, was shown by Giemsa banding, to have a 15/15 chromosome translocation. A review of the literature indicates that such a translocation has only been described once before, in a normal woman, but that chromosme abnormalities in the Prader-Willi syndrome most commonly involve the D group. The significance of this would be clarified by specific chromosome identification in these patients.